Pengaruh Sosial Media Marketing Terhadap Minat Beli Produk Glad2glow Pada Mahasiswa Universitas Muhammadiyah Makassar - Karmila, Karmila; Agus Salim HR; Nurinaya (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of social media marketing on purchase intention toward Glad2Glow products among university students. Social media marketing is measured through the indicators of context, communication, collaboration, and connection, while purchase intention is measured through transactional, referential, preferential, and exploratory intention indicators. Data were collected through questionnaires using a Likert scale distributed to student respondents. The data analysis methods used were descriptive statistics and inferential statistics with a simple linear regression approach processed using SPSS version 24. This research employed a quantitative method with an associative approach. The population consisted of Management Study Program students of the Faculty of Economics and Business, class of 2022, with a total sample of 80 respondents. The analysis was conducted to determine the magnitude of the influence of social media marketing on purchase intention toward Glad2Glow products. The results show that social media marketing has a positive and significant effect on purchase intention, with a t-count value of 14.331 greater than the t-table value of 1.991 and a significance value of 0.000 less than 0.05. The Adjusted R Square value of 0.721 indicates that social media marketing explains 72.1% of the variance in purchase intention, while the remaining 27.9% is influenced by other factors outside the research model. These findings indicate that the more effective the implementation of social media marketing strategies, the higher the students’ purchase intention toward Glad2Glow products. Keywords: Social Media Marketing, Purchase Intention